Public agricultural R&D in South Asia: Greater government commitment, yet underinvestment persists - Stads, Gert-Jan; Rahija, Michael (International Food Policy Research Institute, 2012)
This report analyzes input indicators of public agricultural R&D for five South Asian countries: Bangladesh, India, Nepal, Pakistan, and Sri Lanka. It presents trends and challenges with regard to agricultural R&D investments and human resource capacity throughout the subregion, and provides recommendations for ways to address some of these challenges.